Twenty‐four‐hour growth hormone profiling in the assessment of acromegaly. Issue 1 (27th December 2017) - D'Arcy, Robert; Courtney, C. Hamish; Graham, Una; Hunter, Steven; McCance, David R.; Mullan, Karen
Summary: Objectives and background: Recent guidelines recommend insulin‐like growth factor (IGF‐1), random growth hormone (GH) and nadir GH on an oral glucose tolerance test (OGTT) for assessment of acromegaly. At this Regional Centre, the 24‐hour GH profile has also been used. Design, patients and measurements: We evaluated 57 GH profiles from 34 patients from 2008 to 2012. Samples were drawn every 2 hour and matched with 0800 GH, nadir GH after OGTT and IGF‐1. Results: Correlations between the mean 13‐point profiles and mean 5‐point profile, OGTT nadir and 0800 GH were as follows: r = .99, .99 and .90, respectively ( P < .01 for all). The correlation between the mean 13‐point profiles and IGF‐1 was r = .32 P = .02. Of 5 patients with very high 0800 GH preoperatively (≥20 μg/L), mean 13‐point GH reduced by 88%‐99% postoperatively. IGF‐1 did not normalize in these patients, and all required extra treatment. Preoperatively, all patients had concordant 0800 GH and IGF‐1. Postoperatively, 6 patients had 0800 GH <1 μg/L and high IGF‐1; only 2 of these had a 13‐point mean >1 μg/L, but 5 required further treatment. Conclusions: Growth hormone profiling is not necessary for assessing the majority of patients with acromegaly if there is confidence in the local IGF‐1 assay. When undertaken, a 5‐point profile is adequate. In patients with very high 0800 GH, 24‐hour profiling was useful in demonstrating partial therapeutic success but did not alter management. Further work is needed to explore the possible role of GH profiling in stratifying patients with discordant IGF‐1 and GH results. Abstract : We evaluated the role of 24‐hour growth hormone profiling in the clinical assessment of acromegaly. 57 GH profiles from 34 patients from 2008 to 2012 were matched with 0800 GH, nadir GH after OGTT and IGF‐1. Correlations between measures and clinical outcomes were assessed.